Tractor design and operation for research stations: IITA research guide, No. 4 - Hartley, P. (1998)
The agricultural tractor has passed through a long evolution from the early steam-powered machines to the modern petrol and diesel engine tractors of today. The hydraulic system, power take off, and auxiliary modules have greatly extended the capabilities of tractors. Today, the reliability of tractors depends almost entirely upon proper maintenance. However, tractors are inherently dangerous and must be operated with care.